Electrical and interface state density properties of the 4H-nSiC/[6,6]-phenyl C61-butyric acid methyl ester/Au diode - Aydin, M. E.; Yakuphanoğlu, Fahrettin (Elsevier, 2008)
The electrical and interface state density properties of the Ni/4H-nSiC/PCBM/Au diode have been investigated by current-voltage, capacitance-voltage and conductance-frequency methods. The ideality factor, barrier height and series resistance values of the diode were found to be 2.28, 1.10eV and 3.76 x 10(4) Omega, respectively. The diode shows a non-ideal I-V behaviour with an ideality factor greater than unity that could be ascribed to the interfacial layer, interface states and series resistance. The obtained barrier height (1.10 eV) of the Ni/4H-nSiC/PCBM/Au diode is lower than that of Ni/4H-nSiC diode (1.32 eV). This indicates that the PCBM organic layer induces a change of 160 meV in the barrier height of the Ni/4H-nSiC diode. The interface state density of the diode was determined from G(p)/omega-f plots and was of order of 5.61 x 10(12) eV(-1) cm(-2). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: SiC diode; organic layer; interfacial state density